Rancang Bangun Sistem Informasi Rental Mobil Berbasis Web di AGA Travel Kediri - Husni Mubarok; Izzati, Afifah Nurul; Candra Adipradana; Imam Taufik (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
The development of information technology has had a significant impact on various sectors, including transportation services such as car rentals, which demand operational efficiency and ease of information access. At Aga Travel, the car rental process is still conducted manually, resulting in unstructured data recording, service delays, and difficulties for customers in obtaining vehicle availability information. This study aims to design and develop a web-based car rental information system to address these issues and improve service quality. The development method used is the Waterfall model, which includes stages of requirements analysis, system design, implementation, and testing using Blackbox and User Acceptance Test (UAT) methods. The system was developed using the PHP programming language and MySQL database, equipped with features for online car reservations, real-time vehicle availability checks, payment proof uploads, and administrative management of rental data and revenue reports. The results show that the system can improve transaction management efficiency, accelerate verification processes, and provide easier access to information for customers. UAT testing across various age categories indicated a high level of user acceptance, both in terms of usability and service speed. With the implementation of this system, Aga Travel’s business processes become more structured, fast, and accurate, thus expected to increase customer satisfaction and strengthen the company’s competitiveness in the digital era.